CXCR4‐mediated osteosarcoma growth and pulmonary metastasis is suppressed by MicroRNA‐613. Issue 8 (26th June 2018) - Zhu, Yong; Tang, Lanhua; Zhao, Shushan; Sun, Buhua; Cheng, Liang; Tang, Yifu; Luo, Zhongwei; Lin, Zhangyuan; Zhu, Jianxi; Zhu, Weihong; Zhao, Ruibo; Lu, Bangbao; et al.
Abstract : Osteosarcoma is the most common primary bone malignancy. Recently, studies showed chemokine receptor 4 (CXCR4) played a critical role in osteosarcoma. However, the regulation of CXCR4 is not fully understood. microRNAs are short, non‐coding RNAs that play an important roles in post‐transcriptional regulation of gene expression in a variety of diseases including osteosarcoma. miR‐613 is a newly discovered miRNA and has been reported to function as a tumor suppressor in many cancers. In this study, we confirmed that both Stromal Cell‐Derived Factor (SDF‐1) and CXCR4 could be prognostic markers for osteosarcoma. Meanwhile this study found that SDF‐1/CXCR4 pathway regulated osteosarcoma cells proliferation, migration and reduced apoptosis. Besides, we demonstrated that miR‐613 was significantly downregulated in osteosarcoma patients. Elevated expression of miR‐613 directly suppressed CXCR4 expression and then decreased the proliferation, migration and induced apoptosis of osteosarcoma cells. Moreover, our study found that CXCR4 promoted the development of lung metastases and inhibition of CXCR4 by miR‐613 reduced lung metastases. These data indicated that CXCR4 mediated osteosarcoma cell growth and lung metastases and this effect can be suppressed by miR‐613 through directly downregulating CXCR4. Abstract : SDF‐1/CXCR4 pathway promoted osteosarcoma cells proliferation, migration, and reduced apoptosis. Elevated expression of miR‐613 directly suppressed CXCR4 expression and then decreased the proliferation, migration and induced apoptosis of osteosarcoma cells. CXCR4 promoted the development of lung metastases and inhibition of CXCR4 by miR‐613 reduced lung metastases.